PENGARUH CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR) DAN NON PERFORMING LOAN (NPL) TERHADAP RETURN ON ASSET (ROA) PADA SEKTOR PERBANKAN DI BURSA EFEK INDONESIA - Dwi Fitrianingsih; Anis Fuad Salam; Yolanda Putri; Abdurrohman Abdurrohman (LPPM Universitas Bina Bangsa, 2020)
This research was conducted to determine the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and Non Performing Loans (NPL) on Return On Assets (ROA) both partially and simultaneously in the Banking Sector on the Indonesia Stock Exchange 2014-2018. . The research method is to use the causal associative method, with a quantitative approach. Data collection techniques using secondary data. The sampling technique used purposive sampling technique, the sample was 16 companies which are the annual reports of the banking sector on the Indonesia Stock Exchange (BEI).The results of the study using the t test and f test show that partially the Capital Adequacy Ratio (CAR) has a significant negative effect on Return on Assets (ROA), Loan to Deposit Ratio (LDR) has no significant effect on Return On Assets (ROA), Non-Performing Loan (NPL) has no significant effect on Return On Asset (ROA) and simultaneously Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and Non Performing Loan (NPL) have a significant positive effect on Return On Assets (ROA).